Diagnostic performance of molecular and serological tests of SARS-CoV-2 on well-characterised specimens from COVID-19 individuals: The EDCTP "PERFECT-study" protocol (RIA2020EF-3000) - Joseph Fokam; Claudia Alteri; Luna Colagrossi; Anne-Marie Genevieve; Désiré Takou; Alexis Ndjolo; Vittorio Colizzi; Nicaise Ndembi; Carlo-Federico Perno (PLoS ONE, 2022)
Background The SARS-CoV-2 pandemic is a global threat affecting 210 countries, with 2,177,469 confirmed cases and 6.67% case fatality rate as of April 16, 2020. In Africa, 17,243 cases have been confirmed, but many remain undiagnosed due to limited laboratory-capacity, suboptimal performance of used molecular-assays (~30% false negative, Yu et al. and Zhao et al., 2020) and limited WHO-recommended rapid-tests. Objectives We aim to implement measures to minimize risks for COVID-19 in Cameroon, putting together multidisciplinary highly-experienced virologists, immunologists, bioinformaticians and clinicians, to achieve the following objectives: (a) to integrate/improve available-infrastructure, methodologies, and expertise on COVID-19. For this purpose, we will create a platform enabling researchers/clinicians to better integrate and translate evidence into the COVID-19 clinical-practice; (b) to enhance capacities in Cameroon for screening/detecting individuals with high-risks of COVID-19, by setting-up effective core-facilities on-site; (c) to validate point-of-care SARS-CoV-2 molecular assays allowing same-day result delivery, thus permitting timely diagnosis, treatment, and retention in care of COVID-19 patients; (d) to implement SARS-CoV-2 diagnosis with innovative/highly sensitive ddPCR-based assays and viral genetic characterization; (e) to validate serological assays to identify COVID-19-exposed persons and follow-up of convalescents. Methods This is a prospective, observational study conducted among COVID-19 suspects/contacts during 24 months in Cameroon. Following consecutive sampling of 1,536 individuals, oro/nasopharyngeal swabs and sera will be collected. Well characterised biorepositories will be established locally; molecular testing will be performed on conventional real-time qPCR, point-of-care GeneXpert, antigen-tests and digital droplet PCR (ddPCR); SARS-CoV2 amplicons will be sequenced; serological testing will be performed using ELISA, and antibody-based kits. Sensitivity, specificity, positive- and negative-predictive values will be evaluated. Expected outcomes These efforts will contribute in creating the technical and clinical environment to facilitate earlier detection of Sars-CoV-2 in Africa in general and in Cameroon in particular. Specifically, the goals will be: (a) to implement technology transfer for capacity-building on conventional and point-of-care molecular assays, achieving a desirable performance for clinical diagnosis of SARS-CoV2; (b) to integrate/improve the available infrastructure, methodologies, and expertise on Sars-CoV2 detection; (c) to improve the turn-around-time for diagnosing COVID-19 infection with obvious advantage for patients/clinical management thanks to low-cost assays, thus permitting timely treatment and retention in care; (d) to assess the epidemiology of COVID-19 and circulating-variants in Cameroon as compared to strains found in other countries.